Honour Among Thieves - Archer, Jeffrey (London HarperCollins Publishers, 1994)
The time: 1993. The place: Washington DC. President Bush has just been replaced. In London, Margaret Thatcher has been ousted by her own party. In Russia, Gorbachev has been toppled by forces he cannot control. Of the principal actors in the Gulf War, the sole survivor is Sadam Hussein. Read less
Keywords: Iraq -- Political crimes and offenses -- United States